Glucose Inhibition of Adenylate Cyclase in Intact Cells of Escherichia coli B - Peterkofsky, Alan (1974)
Previous studies in E. coli B have demonstrated an inverse correlation between the presence of glucose in the medium and the accumulation of cyclic AMP in the medium. This observation could not be explained by the action of glucose as a repressor of adenylate cyclase (EC 4.6.1.1) synthesis, as a stabilizer of cyclic AMP phosphodiesterase (EC 3.1.4.17) activity, or as a direct inhibitor of adenylate cyclase activity in cell-free preparations. The recent development of an in vivo assay for adenylate cyclase has provided a basis for further exploring the inhibitory action of glucose in intact cells. With this assay it has been possible to show that, while glucose does not affect adenylate cyclase in vitro, it rapidly inhibits the enzyme activity in intact cells. Extensive metabolism of glucose is not required, since α-methylglucoside also inhibits adenylate cyclase in vivo. When cells are grown on glucose as carbon source, some sugars (mannose, glucosamine) substitute for glucose as adenylate cyclase inhibitors while others (e.g., fructose) do not. Dose-response studies indicate that low concentrations of glucose lead to essentially complete inhibition of adenylate cyclase activity while only moderately decreasing intracellular cyclic AMP concentrations. The evidence presented suggests that the decreased cellular cyclic AMP levels resulting from glucose addition can be accounted for by inhibition of adenylate cyclase without any significant effect on cyclic AMP phosphodiesterase or the transport of cyclic AMP from the cells to the medium.